Peter of Cornwall’s Prologue to Liber disputationum contra Symonem iudeum. Presentation, critical study and translation (Circe de clásicos y modernos, 2021)
In this paper, we offer the translation from Latin into Spanish of Peter of Cornwall’s Prologue to Liber disputationum contra Symonem iudeum (c. 1208), the only section of the text that is currently edited thanks to the labor of Richard W. Hunt. The brief final exchange between the characters of Peter and Simon that Hunt transcribed in the introduction to the edition was added as an annex. These translations are preceded by the presentation of the author and the work as a whole, and by a brief critical study of the text both in itself and in relation to its context of production: the literary dialo-gues of interreligious disputes that flourished between the end of the 11th and the early 13th centuries.
Keywords: interreligious dialogues; disputative dialogues; Peter of Cornawall; Liber disputationum